Effect of aeration on the survival and metamorphosis of scylla serrata (Forskal) from Zoea 1 & Zoea 2. - Pedrajas, Sharon Ann Garganera (1997.)
In the larval rearing of the mud crab, Scylla serrata (Forskal), it is important that the best quality environment be provided in the culture unit to allow maximum survival. In larviculture methods, aeration is either provided or not at all, with inconsistent survival results. This study aimed to find out if aeration or the absence of aeration could affect the survival of zoea 1 and their ability to metamorphose to zoea 2., A 2x3 factorial experiment design was used. A set-up of three optimum stocking densities of 10, 25 and 50 zoea/liter was provided with aeration and was compared to a set-up of the same stocking densities where no aeration was provided. Three replicates were made for each treatment. Feeding monitoring of physico-chemical parameters, and metamorphosis and survival were done everyday, following standard procedures. Two-way analysis of variance (ANOVA) in randomized complete block design (RCBD) was used to analyze the data, to find out if the effect of aeration on survival and metamorphosis is significantly different. Marginal mean comparison was used to find out whether aeration or the absence of it gave better results. Results showed that aeration caused a lower survival probably due to water disturbance which subjected the very fragile and highly sensitive larvae to stress which eventually resulted in their death. Survival and metamorphosis in all stocking densities were found to be not significantly different.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Scylla serrata